The Functions of Fictions: Imagination and Socialization in Both Versions of Keller's Der grüne Heinrich - Hart, Gail Kathleen (The German quarterly, 1986)
The reader-hero, led astray by his uncritical reception of literary fictions, is both novelistic archetype and Realist stereotype. Gottfried Keller repeatedly appropriates this traditional figure in order to reflect on the schism between the active, creative imagination and the normative social reality that contradicts it. A comparison of the two versions of Der grüne Heinrich (1855 and 1880) yields a model for growth as a struggle with letters: both Heinrichs regard literary fictions as verbal allegories of their personal circumstances and each is set the task of relaxing his proprietary grip on literature in order to achieve socialization. The death of Heinrich I and the survival (and socialization) of Heinrich II indicate a certain measure of authorial "growth": the suspicion of imagination and self-loathing of the creative artist which dominate the first version give way to a "both/and" solution in the second, where imagination and social values, though distinct, are no longer mutually exclusive.